2015
DOI: 10.3758/s13423-015-0805-8
|View full text |Cite
|
Sign up to set email alerts
|

Testing a model of componential processing of multi-symbol numbers—evidence from measurement units

Abstract: Research on numerical cognition has addressed the processing of nonsymbolic quantities and symbolic digits extensively. However, magnitude processing of measurement units is still a neglected topic in numerical cognition research. Hence, we investigated the processing of measurement units to evaluate whether typical effects of multi-digit number processing such as the compatibility effect, the string length congruity effect, and the distance effect are also present for measurement units. In three experiments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
2
13
1
Order By: Relevance
“…Close distance trials (1 yuan vs. 5 jiao and 4 yuan vs. 5 jiao) were incompatible trials (yuan > jiao, but 1 < 5 and 4 < 5) and far distance trials (6 yuan vs. 5 jiao and 9 yuan vs. 5 jiao) were compatible trials (yuan > jiao, but 6 > 5 and 9 > 5). In a recent study, Huber et al (2015a) showed that such a compatibility effect can also be shown when comparing physical quantities comprised of a single digit and a unit of measurement suggesting componential processing. Thus, the holistic distance effect found for Chinese prices might be accounted by such a regular compatibility effect instead of indicating that prices might be processed holistically.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Close distance trials (1 yuan vs. 5 jiao and 4 yuan vs. 5 jiao) were incompatible trials (yuan > jiao, but 1 < 5 and 4 < 5) and far distance trials (6 yuan vs. 5 jiao and 9 yuan vs. 5 jiao) were compatible trials (yuan > jiao, but 6 > 5 and 9 > 5). In a recent study, Huber et al (2015a) showed that such a compatibility effect can also be shown when comparing physical quantities comprised of a single digit and a unit of measurement suggesting componential processing. Thus, the holistic distance effect found for Chinese prices might be accounted by such a regular compatibility effect instead of indicating that prices might be processed holistically.…”
Section: Discussionmentioning
confidence: 92%
“…This is useful in case of natural numbers as it assists comparing natural numbers (i.e., a single-digit number, e.g., 3, is always smaller than a two- or three-digit number, e.g., 726). However, considering the number of characters may result in systematic errors in case of decimal numbers (i.e., longer digit strings not necessarily imply larger numbers, e.g., 0.2843 < 0.7; Kallai & Tzelgov, 2014) and units of measurements (e.g., 5 mm <1m; Huber et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the reaction time (RT) for categorization and proportion of “photograph” responses on each photograph proportion. After we excluded the outlier data from the trials in which the RT was outside the mean ± 3 SD ( Ziegler et al, 2001 ; Cohen and German, 2010 ; Constable et al, 2011 ; Chuang et al, 2015 ; Huber et al, 2015 ; Takahashi et al, 2015 ), we calculated the average RT of the categorization of each image. We performed a one-way ANOVA on the RT and defined the images whose RT was significantly longer than those of 0 and 100% as the hard-to-categorize images.…”
Section: Methodsmentioning
confidence: 99%
“…Referring to the former, for text problems it was observed that words associated with an addition procedure (e.g., “more,” “buy”) facilitated processing of text problems requiring additions whereas words associated with subtraction (e.g., “less,” “sell”) interfered with addition problem solving (e.g., Verschaffel et al, 1992 ; see also Daroczy et al, 2015 for a review on linguistic and numerical factors in text problems; Figure 1 , D3). Referring to the latter, place-value processing also seems to be recycled for the processing of measurement units as typical effects observed for two-digit numbers (e.g., unit-decade compatibility effect) were also demonstrated for measurement units ( Huber et al, 2015a ; Figure 1 , D2). Thus, these studies show that magnitude information is not only expressed and processed via Arabic digits and number words but also via other words and symbols which in some cases share processing specificities observed for place-value processing in multi-digit numbers.…”
Section: Integrating Levels Of Linguistic Influences and Place-value mentioning
confidence: 93%